Computational studies of the rotors aerodynamic characteristics of multirotor drones - K. G. Kosushkin; B. S. Kritsky; R. M. Mirgazov (Научный вестник МГТУ ГА)
The article presents the results of computational studies of aerodynamic characteristics for unmanned lift-generating multi-rotor drones of various configurations. The distinctive features of rotors flow were characterized. The rotor interaction was evaluated. The computations were based on the nonlinear rotor blade vortex theory in a non-stationary arrangement. The combinations of four, eight (four coaxial) and fourteen two-bladed rotors at velocity V = 100, 150, 200 km/h were considered. Semi-empirical methods were employed to select the rotor angles of attack, rotation speed, blade installation angles and geometric parameters at the given take-off weight for each combination of rotors and flight airspeed. The computations showed that for a four-rotor lift-generating design (quad-rotor), two rotors installed downstream, depending on the velocity due to the mutual effect, have values of the thrust coefficients ≈10...20% less than those of the rotors located upstream. For a coaxial quad-copter, the effect of the upper front rotor on the upper rear rotor is similar to the effect of the front rotors on the rear ones in a four-rotor lift-generating design. The effect of the upper front rotor on the lower rear rotor does not vary in terms of the average thrust value, and variations are only local in nature. The interaction of other rotors is identical to that of the four-rotor version. A fourteen-rotor lift-generating multi-rotor drone has a complex flow pattern, which generates deviance in the thrust coefficients variation with respect to time. Depending on the mode and rotors location, the average rotor thrust coefficient can vary approximately twice. The computations showed that with the similar geometric parameters and kinematics characteristics, rotors thrust is substantially subject to variation, which causes destabilizing moments to a significant degree without additional control input. Thrust pulsations and, respectively, vibrations grow in intensity as the flight airspeed increases. Probably, the right choice of the rotor configuration and the automatic control system can counterbalance thrust surge by so-called "phasing", i.e. selecting an initial azimuth angle for each rotor.